From Insurgency to Stability Volume II: Insights from Selected Case Studies - Rabasa, Angel (RAND Corporation, 2011)
This book examines six case studies of insurgencies from around the world to determine the key factors necessary for a successful transition from counterinsurgency to a more stable situation. The authors review the causes of each insurgency and the key players involved, and examine what the government did right--or wrong--to bring the insurgency to an end and to transition to greater stability.